Impact of Hydrogen Peroxide on Growth and Survival of Listeria Monocytogenes Biofilms - Farhan Zameer; Shubha Gopal (E-Journal of Chemistry)
The present study aimed to understand the survival strategies adapted by Listeria monocytogenes to combat oxidative stress in planktonic and biofilm cells with response to hydrogen peroxide (H2O2). The sensitivity of L. monocytogenes to H2O2 (oxidative stress) was found to vary in growth cycle. Early log phase cells were found to be sensitive to 100 μM H2O2 when compared to stationary phase. Biofilm population was found to be resistant to the oxidative stress induced at 4% of H2O2 when compared to their planktonic counterpart at 3.5%. This adaptive behavior allows the pathogen to overcome food preservation and safety barriers, which pose a potential risk to human health. The overall results suggest that, H2O2 at a concentration of 6% could be used as a potent sanitizer for the elimination of listerial biofilms.